Personality, Weak Signals, and Workplace Relevant Morality - David L. Dickinson; David Masclet (Institute of Labor Economics (IZA), 2024)
Employers use applicant signals to help solve an asymmetric information problem in organizations. In this paper, we examine the impact of validated Dark versus Light personality traits on incentivized behaviors important to organizations: task effort, honesty, and reciprocity. A second study examined the behavioral impact of two weak signals: regular participation in religious activities (public and private) and a history of time in prison. Study 1 found that Dark relative to Light types were more likely to cheat and shirk in the honesty task, put forth less task effort (i.e., were less productive), but neither type showed evidence for negative cross-task reciprocity (i.e., a spillover from one task to another). In Study 2, ex-Prisoners were more productive than Religious participants in the effort task, and more likely to have shirked in the honesty task. Additionally, ex-Prisoners were more likely to exhibit negative cross-task reciprocity. These findings indicate that both Dark types and ex-Prisoners exhibited behaviors that would be considered undesirable or counterproductive in the workplace, which validates the effectiveness of such characteristics or traits as behavioral signals.
Keywords: C9; D9; M5; 330; experiment; personality traits; honesty; personnel economics; screening; effort